2021
DOI: 10.3390/ijms222212478
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent Changes in Hepatic Sphingolipid Accumulation and PI3K/Akt/mTOR Signaling Pathway in a Rat Model of NAFLD

Abstract: Increased lipid bioavailability in a diet favors lipid accumulation, enhancing hepatic lipotoxicity and contributing to insulin resistance (IR) development. The aim of our study was to examine time-dependent alterations in the intrahepatic content of sphingolipids and insulin signaling pathway in rats fed a high-fat diet (HFD). The experiment was conducted on male Wistar rats receiving a standard diet or HFD for five weeks. At the end of each experimental feeding week, liver sphingolipids were determined using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Sphingolipid signaling pathway is associated with fat accumulation ( 28 ). Inhibiting glycosphingolipid biosynthesis decreased atherosclerosis by inhibiting several enzymes involved in sphingolipid synthesis ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sphingolipid signaling pathway is associated with fat accumulation ( 28 ). Inhibiting glycosphingolipid biosynthesis decreased atherosclerosis by inhibiting several enzymes involved in sphingolipid synthesis ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…VLCFA breakdown occurs in the peroxisome and is required for the synthesis of plasmalogens [ 35 ]. Nervonic acid is mainly stored in hepatic sphingolipids, which are very abundant in the mouse liver [ 12 , 14 , 39 , 40 ]. Indeed, SM d42:2, which consists of the 18-carbon ceramide backbone being sphingosine and a VLCFA of 24 carbons, consistent with nervonic acid (FA 24:1), was elevated in relative abundance in HFCS-HF versus HFCO-HF offspring livers ( p = 0.029, Figure 5 G).…”
Section: Resultsmentioning
confidence: 99%
“…In the presence of excess energy, excessive intake of saturated fatty acids increases plasma and intrahepatic ceramide levels more than polyunsaturated fatty acids [83][84][85]. In the high-fat-fed mice model, the level of intrahepatic ceramides deposition in mice was significantly increased compared to the control group [86], implying that using different dietary patterns could regulate the level of ceramides. In addition, Dong et al found that compared with control mice, hyperhomocysteinemia (HHcy) mice exhibited hepatic steatosis with a notable increase in ceramiderelated metabolites and subsequent upregulation of ceramide synthesis genes.…”
Section: Roles Of Ceramides In Nafldmentioning
confidence: 98%